Excitatory synapses are stronger in the hippocampus of Rett syndrome mice due to altered synaptic trafficking of AMPA-type glutamate receptors - Li, Wei (Proc Natl Acad Sci U S A, 2016)
Deficits in long-term potentiation (LTP) at central excitatory synapses are thought to contribute to cognitive impairments in neurodevelopmental disorders associated with intellectual disability and autism. Using the methyl-CpG-binding protein 2 (Mecp2) knockout (KO) mouse model of Rett syndrome, we show that naïve excitatory synapses onto hippocampal pyramidal neurons of symptomatic mice have all of the hallmarks of potentiated synapses. Stronger Mecp2 KO synapses failed to undergo LTP after either theta-burst afferent stimulation or pairing afferent stimulation with postsynaptic depolarization. On the other hand, basal synaptic strength and LTP were not affected in slices from younger presymptomatic Mecp2 KO mice. Furthermore, spine synapses in pyramidal neurons from symptomatic Mecp2 KO are larger and do not grow in size or incorporate GluA1 subunits after electrical or chemical LTP. Our data suggest that LTP is occluded in Mecp2 KO mice by already potentiated synapses. The higher surface levels of GluA1-containing receptors are consistent with altered expression levels of proteins involved in AMPA receptor trafficking, suggesting previously unidentified targets for therapeutic intervention for Rett syndrome and other MECP2-related disorders.